2018
DOI: 10.3389/fmicb.2018.01585
|View full text |Cite
|
Sign up to set email alerts
|

Whole Cell Cross-Linking to Discover Host–Microbe Protein Cognate Receptor/Ligand Pairs

Abstract: Bacterial surface ligands mediate interactions with the host cell during association that determines the specific outcome for the host–microbe association. The association begins with receptors on the host cell binding ligands on the microbial cell to form a partnership that initiates responses in both cells. Methods to determine the specific cognate partnerships are lacking. Determining these molecular interactions between the host and microbial surfaces are difficult, yet crucial in defining biologically imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The Salmonella adhesion is mediated via protein-carbohydrate or a protein-protein interactions [57], thus proteins and glycosides (SQG and DGG) in alkaline fractions could be synergistically cooperating with polysaccharides binding to bacteria through other mechanisms. For Salmonella Typhimurium, the object of this study, protein-protein interactions are mediated by fimbrial and non-fimbrial adhesins and involve the extracellular matrix components of the host cell [58][59][60][61][62][63]. Several studies reported that milk and colostrum fractions containing proteins (β-lactoglobulin, α-lactalbumin) and glycopeptides (glycomacropeptide) show anti-adherence properties against Salmonella Typhimurium, Salmonella enteritidis, enteropathogenic Escherichia coli, and enterohemorrhagic E. coli, among others [11,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…The Salmonella adhesion is mediated via protein-carbohydrate or a protein-protein interactions [57], thus proteins and glycosides (SQG and DGG) in alkaline fractions could be synergistically cooperating with polysaccharides binding to bacteria through other mechanisms. For Salmonella Typhimurium, the object of this study, protein-protein interactions are mediated by fimbrial and non-fimbrial adhesins and involve the extracellular matrix components of the host cell [58][59][60][61][62][63]. Several studies reported that milk and colostrum fractions containing proteins (β-lactoglobulin, α-lactalbumin) and glycopeptides (glycomacropeptide) show anti-adherence properties against Salmonella Typhimurium, Salmonella enteritidis, enteropathogenic Escherichia coli, and enterohemorrhagic E. coli, among others [11,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota-host interactions happen in almost every known organism, shaping their metabolism and evolution [1,2]. In many ecosystems, the microbiome plays an important role as manifested by its dynamic interactions with different hosts [3].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the metabolite-mediated interactions, protein-protein interactions (PPIs) are one of the most relevant types of molecular interplay between microbes and host organisms [12]. Experimental techniques to test interspecies PPIs are time consuming and have limitations imposed by cost [1,[17][18][19][20][21]. Hence, there is a dearth of validated interspecies PPIs in publicly available databases, and these are mostly limited to pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota-host interactions happen in most organisms, shaping their metabolism and evolution [1][2][3]. In many ecosystems, microbial communities play important roles in the dynamic interactions with the host [4].…”
Section: Introductionmentioning
confidence: 99%
“…Next to metabolite mediated interactions, protein-protein interactions (PPIs) are one of the most relevant and reported types of molecular interactions between the host and microbes [17][18][19][20]. However, experimental techniques to probe inter-species PPIs are time consuming and have limitations imposed by cost [2,14,16,[22][23][24]. Hence, there is a dearth of validated inter-species PPIs in publicly available databases and are mostly limited to pathogens.…”
Section: Introductionmentioning
confidence: 99%